Controlling collapse in Bose-Einstein condensates by temporal modulation of the scattering length - Abdullaev, Fatkhulla Kh. [UNESP]; Caputo, Jean Guy; Kraenkel, Roberto André [UNESP]; Malomed, Boris A. [UNESP] (American Physical Society (APS), 2003)
A study was conducted on the dynamics of 2D and 3D Bose-Einstein condensates in the case when the scattering length in the Gross-Pitaevskii (GP) equation which contains constant (dc) and time-variable (ac) parts. Using the variational approximation (VA), simulating the GP equation directly, and applying the averaging procedure to the GP equation without the use of the VA, it was demonstrated that the ac component of the nonlinearity makes it possible to maintain the condensate in a stable self-confined state without external traps.
Keywords: Approximation theory; Atomic beams; Computer simulation; Electron scattering; Integral equations; Light propagation; Magnetic field effects; Mathematical models; Nonlinear optics; Ordinary differential equations; Perturbation techniques; Solitons; Atomic scattering length; Bose-Einstein condensate; Direct numerical simulation; Gross-Pitaevskii equation; Self-confined condensate; Temporal modulation; Variational approximation; Quantum theory